Pengembangan Pengembangan LKPD berbasis PjBL-STEM pada materi keanekaragaman hayati untuk peserta didik Fase E MAN 1 Kota Padang - billa, salsa; Rahmi, Fitri Olvia; Syamsurizal, Syamsurizal; Kurniati, Rahmi (Al-Alam: Islamic Science Education Journal, 2025)
This research is a development study using the Four-D Model development model. The research instruments used in this study were interview guidelines for teachers, student questionnaires, validity test questionnaires, and practicality test questionnaires. The LKPD was validated by two lecturers from the Department of Biology, FMIPA UNP, one biology teacher, and 28 students from MAN 1 Kota Padang Phase E Academic Year 2025/2026 to test the practicality of the product. Based on the results of the initial and final analysis, the LKPD developed is a PjBL-STEM-based LKPD on biodiversity material for Phase E students. The validity of the PjBL-STEM-based LKPD is 88.64% (highly valid), and the practicality test results by teachers are 90.97% (highly practical) and practicality scores by students are 89.97% (highly practical). The average practicality test results by teachers and students were 90.47% (very practical). Thus, the developed LKPD is highly valid and highly practical.